The management of public finance : a practical guide - Visser, Christiaan Burger; Erasmus, Pieter Wilhelmus (Cape Town, South Africa Oxford University Press, 2002)
This book provides the student with an introduction to financial management, especially of central and provincial government departments. The book is suited to both academics and practitioners.
Includes index.
opc 28/12/16
Loans
Keywords: Finance, Public; Appropriations and expenditures; South Africa